2021
DOI: 10.1149/1945-7111/ac2089
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Aging Behavior of Lithium-Ion Cells Connected in Parallel Considering Varying Charging Profiles and Initial Cell-to-Cell Variations

Abstract: Aging behavior and long-term cell-to-cell variations have been much more frequently investigated in single-cells than cells connected in parallel. In particular, the literature lacks a study investigating the aging behavior of cells in parallel that is based on defined cell-to-cell variations and on the results of a previous single-cell aging study. Moreover, present studies are unable to exclude the impacts of measurement systems on their final results. To counter this deficiency, a novel 4-wire measurement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, the higher uniform of parameters sets a higher screening threshold and results in fewer cells that can be used in groups, which leads to a lower screening efficiency. 32 Furthermore, there is no forced equal current relation in parallel connection and may exist the self-balancing current in a multi-parallel LIBs, 30 which makes it possible for parallel connection to tolerate a certain level of the cell-to-cell variation. As a result, the application of parameter difference has its limitation and especially for the parallel-connected LIBs parameter difference may not be the best option as the screening index.…”
Section: Derivation Of a Novel Screening Index For The Parallel-conne...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the higher uniform of parameters sets a higher screening threshold and results in fewer cells that can be used in groups, which leads to a lower screening efficiency. 32 Furthermore, there is no forced equal current relation in parallel connection and may exist the self-balancing current in a multi-parallel LIBs, 30 which makes it possible for parallel connection to tolerate a certain level of the cell-to-cell variation. As a result, the application of parameter difference has its limitation and especially for the parallel-connected LIBs parameter difference may not be the best option as the screening index.…”
Section: Derivation Of a Novel Screening Index For The Parallel-conne...mentioning
confidence: 99%
“…z E-mail: y_wangfdu@fudan.edu.cn; yjSun@fudan.edu.cn On the contrary, the short board effect is not fully applicable to guide the screening process of parallel-connected LIBs, mainly because the current of each parallel branch is not forced to be equal. 30 In some study, it is assumed that all parallel cells undergo similar currents due to the common voltage of the parallel cells, 31 but in reality, it is the fact that the cell-to-cell parameters are relatively consistent and thus bring similar currents, which is not the result of the common voltage. Furthermore, as there is the selfbalancing current in a multi-parallel LIBs, 30 it is possible for parallel connection to tolerate a certain level of the cell-to-cell variation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most normal cells, a small number of cells could grow, divide and proliferate, and the tumor cell has the significant biological characteristics, including selfgrowth, insensitive to growth inhibition and periodic proliferation, so that the tumor cell proliferation may threaten the life [11] . In the research, the CCK-8 test is carried out to detect the influence of esomeprazole on the hepatoma cell proliferation.…”
Section: Group N Inhibition Ratio (%) 24 H 48 H 72 Hmentioning
confidence: 99%
“…The behavior of parallel-connected batteries has been explored empirically by Luca et al (2021); Schindler et al (2021); Diao et al (2019), who independently demonstrated the potentially significant impact of mismatched resistances and capacities on the current imbalance at the end of a charge cycle. Model-based approaches have also been proposed for pack-level simulations and controls.…”
Section: Introductionmentioning
confidence: 99%